KEMAMPUAN MANAJERIAL KEPALA SEKOLAH DALAM PENINGKATAN EFEKTIVITAS PERPUSTAKAAN SEKOLAH - Galuh Eknasia Hapsari (Manajer Pendididikan, 2016)
The general purpose this research to describes the principal managerial ability toward to effectiveness increasing the school library. The method of this research use descriptive qualitative.The result of this research these are: (1) the useful school library planning that had done by stakeholders and students. (2) the school library useful program at elementary school 06 Ketahun district North Bengkulu as the only one of source learning that available of books. (3) the evaluation of school library useful to know the planning goals program. (4) the spirit and thebarrier principals managerial to make effective of school library at elementary school 06 Ketahun district North Bengkulu.Keywords: principal, managerial, effectiveness, library